2022
DOI: 10.29333/iji.2022.15324a
|View full text |Cite
|
Sign up to set email alerts
|

Information System for Monitoring and Management of the Quality of Educational Programs: Development of Functioning Algorithms

Abstract: The study develops a method for monitoring and management of the quality of educational programs using software instruments. The method describes each of the monitoring implementation stages in detail specifying the input and output data, as well as the controls that affect the time and quality of the implementation of the corresponding stage. Algorithm programs in the form of flowcharts reflecting all the content aspects are developed and formalized for the automatization of monitoring. The presented algorith… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
19
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(20 citation statements)
references
References 21 publications
1
19
0
Order By: Relevance
“…In their works Logachev et al (2022a) and Alajali et al (2018) note the importance of obtaining such parameters, on the basis of which mathematical models describing certain processes of the problem area are developed. It should be noted that in the works of Nikitina [5], the regulation of traffic and pedestrian flows in order to reduce the downtime of transport within the simulation model allows to estimate the levels of environmental pollution. The work performed by our team does not contradict such studies as Buneev (2018), Zeng (2018), but complements and allows the simulation of different environmental scenarios in the area.…”
Section: Discussionmentioning
confidence: 99%
“…In their works Logachev et al (2022a) and Alajali et al (2018) note the importance of obtaining such parameters, on the basis of which mathematical models describing certain processes of the problem area are developed. It should be noted that in the works of Nikitina [5], the regulation of traffic and pedestrian flows in order to reduce the downtime of transport within the simulation model allows to estimate the levels of environmental pollution. The work performed by our team does not contradict such studies as Buneev (2018), Zeng (2018), but complements and allows the simulation of different environmental scenarios in the area.…”
Section: Discussionmentioning
confidence: 99%
“…The realisation of the educational process with the use of digital technologies extends the capabilities of all its participants, meets the learners' modern needs, increases motivation for cognitive activity, promotes optimisation of pedagogical work and educational activities [2,11,13]. The scholars note in their works that the use of information technologies in the educational process is characterised by the holistic unity of motivational, cognitive, and activity-based components [12,14].…”
Section: Discussionmentioning
confidence: 99%
“…The operational management of a project is organised this way. When analysing a number of contemporary works connected with software products, the team of authors presenting this article found that the method of analysis proved to be a key tool [3,10,11].…”
mentioning
confidence: 99%
“…The problem of information protection is of interest to scholars of various branches of science: programming, computer networks, and information protection (Sedova et al, 2023;Neverov et al, 2022), law (Pauzin et al, 2022), information security management . Thus, we note that this problem is mainly dealt with by specialists in the field of physical and mathematical (Tolmachev et al, 2022) and technical (Logachev et al, 2022) sciences, whose research is intended for official use, since it contains technical developments of information security systems. information security specialists (Skripak et al, 2022).…”
Section: Literature Reviewmentioning
confidence: 99%